Duration of toothbrushing with fixed appliances: a randomized crossover clinical trial. (24th November 2021) - Koretsi, Vasiliki; Klinke, Rebecca; Herreiner, Philip; Proff, Peter; Kirschneck, Christian
Summary: Objective: Fixed orthodontic appliances might result in dental adverse effects, if sufficient oral hygiene is not maintained. Since recommendations on toothbrushing times are lacking scientific justification in orthodontic populations, the aim of the present study was to comparatively quantify the duration of toothbrushing with a manual and a powered toothbrush in two distinct age groups. Trial design: Two-centre, two-period crossover balanced randomized clinical trial with computer-generated numbers and blinding at the outcome-assessing level. Methods: Children and adults with fixed appliances with at least 22 aligned teeth were recruited at a university clinic and private practice in Bavaria, Germany. Plaque was disclosed with staining tablets and participants brushed their teeth with their habitual technique in front of a mirror and without interference until staining was, to their own satisfaction, completely removed. The primary outcome was duration of toothbrushing in seconds. Secondary outcomes were percentage plaque reduction and questionnaire data on dental attitudes and behaviours. Data were analysed with linear mixed models. Results: Twenty-eight participants were randomized to the first and 27 to the second toothbrush sequence. The combined effect of age and toothbrush on the duration of toothbrushing was evident ( n = 52, F (1, 50.8) = 5.1, P = 0.028). Children brushed 14.5 seconds less [ n = 28, 95% confidence interval (CI) = −31.3 to 2.3, P = 0.090], yet adults 13.3 seconds more ( n = 24, 95% CI = −4.6 to 31.3, P = 0.143) with the manual than powered toothbrush. Brushing times ranged from 2 minutes and 45 seconds to 3 minutes and 17 seconds with plaque reduction at 76% and good dental attitudes and behaviours. Conclusions: Both children and adults with fixed appliances might equally reach an effective plaque reduction with either manual or powered toothbrushes and their habitual brushing technique in around three minutes, if plaque is visible. Registration: DRKS—German Clinical Trials Register ID: DRKS00012463. Funding: Oral-B Procter & Gamble.